Corporate law and economic stagnation : how shareholder value and short-termism contribute to the decline of the Western economies - Masouros, Pavlos E. (Netherlands : Eleven International Publishing, 2013)
The shift in the institutional logics of corporate governance towards shareholder value coupled with shareholdership's increasing short-termism have cumulatively contributed to the low GDP growth rates that are observed in five major Western economies (France, Germany, The Netherlands, UK, US) since the breakdown of the Bretton Woods system in the 1970s. This book presents - through empirical data and with the help of the post-Keynesian theory of the firm - a historical causality chain: The two Great Reversals led to higher equity payout ratios and lower retention ratios in public corporations that in turn caused lower growth rates of (business) capital accumulation that in turn caused lower GDP growth rates. Corporate law has been an accomplice for the reorientation of corporate governance towards shareholder value, i.e. for the Great Reversal in Corporate Governance, and thus it indirectly shares the blame for the low rates of capital accumulation that have thrown the five major Western economies in a stagnation mode over the past four decades.
Corporate governance and international political economy : how changes in the international monetary order brought about the great reversal in corporate governance and the great reversal in shareholdership -- Modeling short-term shareholdership's negative impact on the dynamics of capital accumulation : the post-Keynesian theory of the firm -- Corporate law's contribution to the great reversal in corporate governance -- Corporations and shareholder eugenics : how corporate law sustains the great reversal in shareholdership -- The path towards long governance.
"Progress stagnation"--Cover.
Includes bibliographical references and index.
Keywords: Corporation law; Corporation law -- Economic aspects; Social responsibility of business; Law and economics